On Ideal Convergence of Sequences of Functions in Intuitionistic Fuzzy Normed Spaces - Karakaya, Vatan; Simsek, Necip; Erturk, Muzeyyen; Gursoy, Faik (NATURAL SCIENCES PUBLISHING CORP-NSP, 2014)
In this work, our purpose is to introduce I-convergence of sequences of functions in intuitionistic fuzzy normed space by combining the I-convergence, the sequences of functions and the intuitionistic fuzzy normed spaces, and to investigate relations among concepts such as I-convergence, statistical convergence and the usual convergence of sequences of functions in intuitionistic fuzzy normed space.
Keywords: I-Uniform convergence; Sequences of function; Intuitionistic Fuzzy Normed Space; STATISTICAL CONVERGENCE; I-CONVERGENCE; Mathematics; Physics